'Interpreting Buddhist Precepts with Confucian Rites' Based on Their Similarity and Dissimilarity: A Perspective of the History of Ideas in Wei, Jin, and Northern and Southern Dynasties - Shengkai (Religions, 2022)
The “similarity” (gongtong 共通) and “dissimilarity” (chayi 差異) between the Buddhist precepts and Confucian rites in the Wei, Jin, and Southern and Northern Dynasties reflected a “dialogue of civilizations” (wenming duihua 文明對話) at the levels of concept, system, and life. During these periods, the Chinese system of rites were compared and interpreted with the Buddhist monastic codes by Buddhist monks and Confucian scholars, so a history of the ideas interpretation process of “interpreting precepts with rites” (yi li shi jie 以禮釋戒) was achieved. The result of such a process was two-fold: from the perspective of lay Buddhist ethics, they were in common with each other; from the perspective of monastic precepts, they were irreconcilable contradictions. Thus, on the one hand, the eminent Chinese monks “were emulating the Confucian rites to justify Buddhist precepts” (ni li yi zheng jie 擬禮義證戒) to stress their commonalities. On the other hand, the differences between the precepts and rites continued to be discovered, and the Buddhist subjective consciousness (zhuti yishi 主體意識) of “the distinction between precepts and rites” (jie li you bie 戒禮有別) was gradually established.